The oceanic concordance of phylogeography and biogeography: a case study in Notochthamalus. Issue 13 (7th June 2016) - Ewers‐Saucedo, Christine; Pringle, James M.; Sepúlveda, Hector H.; Byers, James E.; Navarrete, Sergio A.; Wares, John P.
Abstract: Dispersal and adaptation are the two primary mechanisms that set the range distributions for a population or species. As such, understanding how these mechanisms interact in marine organisms in particular – with capacity for long‐range dispersal and a poor understanding of what selective environments species are responding to – can provide useful insights for the exploration of biogeographic patterns. Previously, the barnacle Notochthamalus scabrosus has revealed two evolutionarily distinct lineages with a joint distribution that suggests an association with one of the two major biogeographic boundaries ( 30°S) along the coast of Chile. However, spatial and genomic sampling of this system has been limited until now. We hypothesized that given the strong oceanographic and environmental shifts associated with the other major biogeographic boundary ( 42°S) for Chilean coastal invertebrates, the southern mitochondrial lineage would dominate or go to fixation in locations further to the south. We also evaluated nuclear polymorphism data from 130 single nucleotide polymorphisms to evaluate the concordance of the signal from the nuclear genome with that of the mitochondrial sample. Through the application of standard population genetic approaches along with a Lagrangian ocean connectivity model, we describe the codistribution of these lineages through a simultaneous evaluation of coastal lineage frequencies, an approximation of larval behavior, and current‐driven dispersal. Our results show that this pattern could not persist without the two lineages having distinct environmental optima. We suggest that a more thorough integration of larval dynamics, explicit dispersal models, and near‐shore environmental analysis can explain much of the coastal biogeography of Chile. Abstract : Two divergent lineages of the barnacle Notochthamalus scabrosus are found along the coast of Chile; the overlapping distribution of these lineages closely mirrors the broader biogeographic patterns of the intertidal fauna. Using mitochondrial sequence and nuclear SNP data comprising 131 loci, we fully characterize this distribution along the entire coast of Chile and use an ocean connectivity model to explore likely environmental transitions that maintain these distributions.